Community pursuing the dream, living the reality - Keller, Suzanne (Princeton studies in cultural sociology, 2003)
This book tells the story of how a human community comes to be and how aspirations for the good life confront the dilemmas and detours of real life. Suzanne Keller combines penetrating analysis of classic ideas about community with a remarkable and unprecedented thirty-year case study of one of the first "planned unit developments" in America and the first in New Jersey. (Pub. description).